Nadroparin carries a potentially high risk of inducing cutaneous delayed‐type hypersensitivity responses. (14th March 2017) - Schindewolf, Marc; Recke, Andreas; Zillikens, Detlef; Lindhoff‐Last, Edelgard; Ludwig, Ralf J.
Summary: Background: Heparins are widely used for the prophylaxis/treatment of thromboembolic events. As adverse effects, heparin‐induced skin lesions occur frequently (in 7.5–39% of patients). Skin lesions may be the only clinical manifestation of life‐threatening immune‐mediated heparin‐induced thrombocytopenia, but are commonly caused by a delayed‐type hypersensitivity response [heparin‐induced delayed‐type hypersensitivity (HIHS)]. Risk factors have not been prospectively identified. Objectives: To identify possible risk factors for heparin‐induced skin lesions from three independent clinical trials in a combined analysis. Methods: A pooled analysis from prospective studies was performed, and possible risk factors were included in a multiple logistic regression analysis. Results: Obesity (body mass index of > 25), prolonged anticoagulant therapy, prior heparin exposure and younger age (< 55 years) were confirmed as independent risk factors for HIHS. The choice of anticoagulant preparation had the greatest influence. On comparison of dalteparin, enoxaparin, fondaparinux, unfractionated heparin, and nadroparin, the latter was associated with the highest risk of eliciting HIHS (odds ratio of 30.2, 95%CI: 11.7–77.9). Conclusions: The high risk associated with nadroparin has been validated in controlled trials, and this emphasizes the singularity of each heparin preparation in terms of allergenicity and that individualized anticoagulation is required.